Systematic Literature Review: GPU, TPU, FPGA dalam Akselerasi AI - Siska Fitriani; Ega Budiman; Muhammad Fadli; Amarudin Amarudin (STMIK Banjarbaru, 2026)
The increasing complexity of artificial intelligence (AI) models has raised the demand for efficient hardware accelerators. A key challenge is selecting an accelerator that aligns with application needs, as mismatches can affect energy efficiency, inference speed, and system scalability. GPU, TPU, and FPGA are the most commonly used accelerators in AI deployment, each with specific advantages and limitations. This study aims to systematically evaluate the utilization of these three accelerators across various AI domains. A Systematic Literature Review (SLR) was conducted using the Kitchenham framework, analyzing 20 scientific articles. Results show that GPUs are used in 90% of studies, TPUs in 50%, and FPGAs in 70%. In terms of energy efficiency, FPGAs are superior in 78% of the relevant articles, while GPUs dominate inference performance in 85% of cases. This study concludes that selecting an AI accelerator should be guided by power efficiency, system architecture, and domain-specific requirements. The findings offer practical implications for graduate students in selecting appropriate accelerators that align with their research topics, experimental goals, and resource constraints in AI-driven thesis projects.Keywords: Artificial Intelligence Accelerator; Graphics Processing Unit; Tensor Processing Unit; Field Programmable Gate Array; Systematic Literature Review AbstrakPerkembangan model kecerdasan buatan (AI) yang semakin kompleks menimbulkan kebutuhan akan akselerator perangkat keras yang efisien. Masalah utama yang sering dihadapi adalah pemilihan akselerator yang tidak sesuai dengan kebutuhan aplikasi, yang berdampak pada efisiensi daya, kecepatan inferensi, dan skalabilitas sistem. GPU, TPU, dan FPGA merupakan tiga jenis akselerator yang paling banyak digunakan dalam implementasi AI, Penelitian ini bertujuan mengevaluasi pemanfaatan ketiga akselerator dalam berbagai domain AI menggunakan Systematic Literature Review (SLR) berbasis pendekatan Kitchenham. Sebanyak 20 artikel diseleksi dari lima basis data ilmiah terkemuka. Hasil menunjukkan GPU digunakan dalam 90% studi, FPGA dalam 70%, dan TPU dalam 50%. FPGA unggul dalam efisiensi energi (78% studi), sementara GPU dominan dalam performa inferensi (85% kasus). Penelitian menyimpulkan pemilihan akselerator AI harus mempertimbangkan efisiensi daya, arsitektur sistem, dan kebutuhan domain. Temuan ini memberikan panduan praktis bagi mahasiswa magister dalam memilih akselerator sesuai topik, tujuan eksperimen, dan keterbatasan sumber daya.Kata Kunci: Akselerator Artificial Intelligence; Graphics Processing Unit; Tensor Processing Unit; Field Programmable Gate Array; Tinjauan Sistematik